Coordination assembly and host–guest chemistry of a triply interlocked [2]catenane. Issue 9 (24th March 2021) - Yu, Weibin; Qiu, Feng-Yi; Luo, Shi-Ting; Shi, Hua-Tian; Yuan, Guozan; Wei, Xianwen
Abstract : Triply catenated systems composed of two or more discrete coordination-metal cages through mechanical bonds exhibit excellent host–guest behaviors, which can be potentially applied in drug delivery systems. Abstract : Triply catenated systems are highly intricate topologies that consist of two identical, mechanically interlocked coordination cage components with intriguingly complex architectures. A few triply interlocked catenanes have been successfully synthesized to date, but how to controllably construct the aesthetic topologies and study their host–guest properties is still a tough challenge. Herein, taking advantage of rational strategies, we reported the efficient construction of a triply interlocked [2]catenane with the formula [(Cp*Rh)12 B6 L4 ](OTf)12, wherein both the discrete metal-coordination cages were mutually interlocked through mechanical bonds. A series of characterization techniques were employed to confirm the formation and structure of the desired triply interlocked system: multinuclear NMR spectroscopy, ESI-MS, and single-crystal X-ray diffraction analysis. The solid-state structure of [(Cp*Rh)12 B6 L4 ](OTf)12 unambiguously confirmed the existence of a triply interlocked catenane that consisted of two identical, mechanically interlocked hexanuclear metal-coordination cage components. Interestingly, in solution, the catenated topology can be transformed into a monomer induced by host–guest interactions and external stimuli like UV-visible light. Furthermore, we systematically studied its host–guest properties for potential applications in drug delivery systems.